Evaluation on the stability of slope at Faculty of Engineering and Built Environment (FKAB) using Slope/w - Salmah Salween,; Khairul Anuar Mohd Nayan,; Mohammad Omar Faruk Murad, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Slope stability topics have become one of the main issues due to the nature of topography and weather conditions in Malaysia. This study examines the stability of the slope at the Faculty of Engineering and Built Environment (FKAB) and eventually to identify the best approach for the analysis. The three main objectives of this study are to evaluate the slope of FKAB using the Limit Equilibrium method, using Slope/w to evaluate the critical soil parameters obtain through back analysis, and eventually to obtain the best method to be use for further analysis on the stability of slope. The steps involve in solving the model of the slope were drawn, defined and assigned accordingly before the final analysis is being carried out in accordance to the methodology of the Slope/w 2007 software. The minimum Factor of Safety (FOS) obtained from the analysis using the unsaturated soil model were found to be 0.999, 1.001 and 1.002 from the Janbu Method, Ordinary Method, Bishop Method and Sarma Method respectively. These Factor of Safety (FOS) were obtained by using back analysis of a two layered model. Layer 1 with soil parameters of 18 kN/m³ of unit weight, 90 kPa of cohesion and 20° of angle of friction were assigned. Correspondingly for layer 2, the values of 15 kN/m³ unit weight above the groundwater table and 18 kN/m³ below groundwater table, 3 kPa of cohesion and 8° of angle of friction were assigned. In this study, the Sarma Method was found to be the best method as it satisfies both force and moment equilibrium and is recommended for further analysis to be taken at the slope.